2018
DOI: 10.1103/physrevb.97.104424
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of the S=12 random Heisenberg chain

Abstract: We study dynamical properties at finite temperature (T ) of Heisenberg spin chains with random antiferrormagnetic exchange couplings, which realize the random singlet phase in the low-energy limit, using three complementary numerical methods: exact diagonalization, matrix-product-state algorithms, and stochastic analytic continuation of quantum Monte Carlo results in imaginary time. Specifically, we investigate the dynamic spin structure factor S(q, ω) and its ω → 0 limit, which are closely related to inelasti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 79 publications
(187 reference statements)
2
37
2
Order By: Relevance
“…The SAC method we use here is the standard form that uses a parametrization of the spectral function with a large number of equal-amplitude δ functions [19,20]. The inverse of the Laplace transform in Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAC method we use here is the standard form that uses a parametrization of the spectral function with a large number of equal-amplitude δ functions [19,20]. The inverse of the Laplace transform in Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Since S (q, ω) can be accessed directly by INS and nuclear magnetic resonance (NMR) experiments, the most favorable evidence for the validity of the QMC-SAC method is that the calculated S (q, ω) results are in good agreement with the existing experimental results [19]. As an effective numerical method for calculating the complete spectra, the QMC-SAC method has recently been used in some interesting work, such as the spin excitation spectrum of the random singlet state [20], quantum spin liquids [13], the dynamical signature of fractionalization at a deconfined quantum critical point [12], and the dynamics of the Higgs mode in spin systems [21,22]. However, unlike the results given by analytical studies, the effects of various modes of spin excitation are intermingled in the results obtained with QMC-SAC.…”
Section: Introductionmentioning
confidence: 94%
“…What exactly happens when a regular spinchain is exposed to an increasing degree of disorder is not well known. Until recently, progress has been slow as far as numerical simulations 13 and, especially, experimental investigations [14][15][16] of disordered low-dimensional systems are concerned. The main reasons include computational difficulties due to the large size of realistic disordered systems and, regarding experiments, the scarcity of suitable systems in which disorder can be easily tuned over a broad range without changing the structural character of the material.…”
Section: Introductionmentioning
confidence: 99%
“…For uncorrelated disorder, we have proposed and numerically verified that the correlations in Eqs. (7), (10), (16) are good approximations in the regime γ D r ≫ 1 (not restricted to the thermodynamic limit r ≪ L) for periodic boundary conditions. We have shown that the chord length (8) is not the true scaling variable exhibiting small corrections for the mean correlations and even smaller for the typical ones.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that for smaller values of D, the slope A α is not fully saturated (due to the effects of the crossover 7 We consider only the data such that C xx typ < 2.5 10 −2 and C zz typ < 2.0 10 −4 . This is simply to ensure some meaning to the fitting function (16) when disorder is weak (D < 0.6). As we explain latter on, this has no influence in our results.…”
Section: Iii2 Typical Correlation Function and Probability Distribumentioning
confidence: 99%